1964
DOI: 10.1002/j.1537-2197.1964.tb06703.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Organized Development of Cultured Cells. Vii. Cellular Variation

Abstract: Variation in long‐continued cultures of Haplopappus gracilis and Daucus carota has been investigated. A strain of carrot tissue was isolated that grew with a compact habit, in contrast to the highly friable habit of the parent strain. Its dividing cells were arranged quite differently than in the parent strain. Earlier work had shown that Haplopappus cultures could be reversibly altered in their pigmentation and form, by changing the culture medium. This was confirmed, and it was further shown that pronounced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1964
1964
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The present H. gracilis callus seems to be fairly stable as compared with other examples of H. gracilis callus (Blakely andSteward 1964, Ashmore andShapcott 1989) and calluses of other plant species (Ogura 1990). About 2% of aneuploid cells were observed in total, however, no clear differences were recognized in increase or decrease n in Fig.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…The present H. gracilis callus seems to be fairly stable as compared with other examples of H. gracilis callus (Blakely andSteward 1964, Ashmore andShapcott 1989) and calluses of other plant species (Ogura 1990). About 2% of aneuploid cells were observed in total, however, no clear differences were recognized in increase or decrease n in Fig.…”
Section: Methodssupporting
confidence: 60%
“…Some studies reported that the majority of cells in Haplopappus gracilis callus retained the chromosome number of normal controls, 2n=4 (Kao et al 1970, Singh et al 1975, whereas some stressed an appearance of aneuploid cells in callus of a particular strain of H. gracilis (Blakely andSteward 1964, Ashmore andShapcott 1989). To our knowledge, however, few studies have been performed as to the difference of changeability of each chromosome in H. gracilis callus.…”
mentioning
confidence: 99%
“…In terms of the chromosomal constitution of the regenerated plants from callus cultures, the results of cytological observations are classified into the following two types; the eudiploid or polyploid constitution of original regenerates (Mitra et al 1960;Blakely and Steward 1964;Venketeswaran and Spiess 1964;Singh et al 1972;Novak and Vyskot 1975 and others) and the aneuploid constitution of the regenerates (Tabata et al 1968;Niizeki and Grant 1971;Melchers and Labib 1974;Smith et al 1976 and others) as well as the somatic chromosomal chimerism of the regenerates (mainly in the Nicotiana and Saccharum species) (Sacristan and Melchers 1969;Heinz et al 1969;Heinz and Mee 1971;Collins et al 1972;Ogura 1975aOgura , 1976Liu and Chen 1976 and others) . The different results may be due to nature of the species used, culture conditions and other unknown causes.…”
Section: Discussionmentioning
confidence: 99%
“…yama and Taira 1966, Shimada and Tabata 1967), Daucus cayota (Muir 1965), Sacchayum (Heinz et al 1969), Vicia faba and Allium cepa (Yamane 1975), and comparatively small in Triticum aestivum (Shimada et al 1969;Asami et al 1972Asami et al , 1975Inomata et al 1975;Okamoto et al 1975b), Haplopappus gracilis (Mitra andSteward 1961, Blakely andSteward 1964;Kaneko 1974), Crepis capillaris (Sacristan and Wendt-Gallitelli 1973), some Sacchayum (Heinz et al 1969), Haworthia (Yamabe and Yamada 1973).…”
mentioning
confidence: 99%